PENGARUH KUALITAS PRODUK, BRAND IMAGE, DAN KEPERCAYAAN MEREK TERHADAP KEPUASAN PELANGGAN SKINCARE AVOSKIN - Rizky Rahma Aulia Putri; Edy Purwo Saputro (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to investigate how product quality, brand image, and brand trust affect consumers' satisfaction with Avoskin Skincare. Quantitative research methodology is applied. Analysis of data with Smart PLS 3.0. Direct distribution of questionnaires to respondents is how data collecting is carried out. Students from Muhammadiyah University of Surakarta's Faculty of Economics and Business participated in this study as respondents, with a sample size of 100 individuals. The study's findings demonstrate that consumer satisfaction is positively impacted by the factors of product quality and brand trust. On the other hand, there is no correlation and no significance between the brand image and customer satisfaction variables.